201k views
0 votes
Simplify the following expression.

99 - 3[15 - (2 + 1)]

User Ram Sharma
by
5.6k points

2 Answers

2 votes

Steps

99-3(15-(2+1))

3(15-(2+1))=36

add the numbers: 2+1=3

=3(15-3)

Subtract the numbers: 15-3=12

=3 times 12

multiply the numbers: 3 times 12=36

=36

=99-36

subtract the numbers: 99-36=63

=63

User Sean Van Gorder
by
4.7k points
4 votes

Answer:

63

Explanation:

2+1= 3

15-3= 12

12 x 3 = 36

99 - 36

= 63

User Izabel
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.